Effect of nutrient level on phytoplankton population in zero water exchange shrimp culture farms - Ramamoorthy, Saraswathy; Moturi, Muralidhar; Pitchaiyappan, Ravichandran; Ponniah, Alphis Gitanand; Akshaya, Panigrahi; Muniyandi, Kailasam; Arunachalam, Nagavel (Indian Journal of Fisheries, 2012)
Soil and water characteristics and their influence on phytoplankton abundance, at different stocking densities under zero water exchange were studied in two successive crops of tiger shrimp, Penaeus monodon at Mahabalipuram, Kanchipuram District in Tamil Nadu, India during 2007 and 2008. The shrimp ponds were categorised under two groups viz.. low stocking density (8 no. m-2) and high stocking density (16 no. m-2). In pond water, physico-chemical properties and total nutrient content did not vary significantly between the stocking densities, whereas nitrate and phosphate significantly differed. All available and total nutrients viz., nitrogen, phosphorus and silicate increased significantly in pond water with days of culture. Water quality had an influence on the abundance of phytoplankton and it varied widely and significantly during culture period as well as with different stocking densities. Phytoplankton density had a positive correlation with nitrate (r=0.87), phosphate (r=0.79), silicate (r=0.97) and chlorophyll a content (r=0.98).